Novel resin-based silicon carbide / graphite / nickel composite wave-absorbing material and preparation method thereof
Through mechanical ball milling and selective laser sintering technology, combined with vacuum pressure immersion technology, silicon carbide/graphite/nickel composite wave absorbing material was prepared, which solved the problem of difficulty in synergizing the wave absorbing performance and mechanical properties in traditional processes, and achieved the coordination of multiple loss mechanisms and excellent electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202411905449.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional processes are difficult to achieve controllable assembly of multiple absorbents, resulting in a single loss mechanism and difficulty in coordinating the absorption and mechanical properties.
The porous graphite preform was prepared by mechanical ball milling and selective laser sintering, and through curing and vacuum pressure immersion processes, combined with a multi-combination of silicon carbide, graphite and nickel, the SiC/NFG/Ni@MC/PF/EP composite wave absorbing material was formed.
The coordination of conductivity, dielectric and magnetic losses is achieved, the electromagnetic wave loss capability is improved, and the electromagnetic wave attenuation is significantly promoted through the heterogeneous interface polarization effect, and excellent mechanical properties and wave absorption characteristics are obtained.
Smart Images

Figure CN119653754A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave absorbing material development, and in particular to a novel resin-based silicon carbide / graphite / nickel composite absorbing material and a preparation method thereof. Background Art
[0002] The rapid development of the Internet and electronic devices has profoundly improved people's lives, providing unprecedented convenience, speed and comfort. However, it has also brought about problems related to electromagnetic pollution. The development of efficient microwave absorbing materials has become a top priority.
[0003] Single absorbers are mainly suitable for application scenarios with relatively simple or known requirements for absorbing performance, such as ordinary radar absorbing materials. Multi-component absorbers are mainly used in scenarios that require special performance, such as high-frequency absorbing materials or absorbing materials that can work in specific environments. Compared with traditional single absorbers, composite absorbers achieve material variability, assemblability, adjustable comprehensive performance, and coordination of multiple loss mechanisms. The key technical difficulty lies in the manufacturing process, and it is particularly urgent to explore simpler and more effective manufacturing process strategies. The main forming methods of domestic multi-component absorbing materials include sol-gel method, electrospinning combined with high-temperature pyrolysis method, hydrothermal method and lamination method.
[0004] The sol-gel method controls the chemical reaction in the solution so that the solute atoms or ions form a stable sol system, which is then converted into a solid gel through a gelation process, and finally the desired absorbing material is obtained through drying and heat treatment. The prepared composite absorbing material has a good application in radar stealth technology. However, this method has high raw material cost, long process time, large shrinkage, and easy agglomeration problems. The electrospinning combined with high-temperature pyrolysis method uses electrostatic force to stretch polymer solution or melt to form ultrafine fibers, and improves the structure and performance of the material through high-temperature pyrolysis; the prepared composite absorbing material has a good application in the field of high-performance electromagnetic protection. The preparation process of this method is complex, costly, and has poor mechanical properties. The hydrothermal method is a technology that uses water as a solvent to carry out chemical reactions under high temperature and high pressure conditions in a sealed pressure vessel. The absorbing material prepared by this method has certain corrosion resistance; however, due to the limitations of preparation cost and process conditions, the research on many composite absorbing materials is still in the laboratory stage and has not been widely used in industry. The lamination method stacks different materials together and firmly combines them into a whole using heat, pressure or other bonding methods. The prepared composite absorbing material is particularly important in the fields of aerospace, etc.; however, this method cannot meet the demand for lighter and thinner materials. Summary of the invention
[0005] Purpose of the invention: In view of the fact that traditional process methods are difficult to achieve controllable assembly of multiple absorbers, resulting in a single loss mechanism and difficulty in coordinating absorbing performance and mechanical properties, a new resin-based silicon carbide / nickel / graphite composite absorbing material and its preparation method are proposed.
[0006] Inventive concept: First, a porous graphite preform is quickly prepared by mechanical ball milling and selective laser sintering. The curing and vacuum pressure impregnation process not only improves the mechanical properties of the composite material, but also couples the magnetic material (Ni) into the NFG / SiC composite material to obtain a SiC / NFG / Ni@MC / PF / EP composite absorber. This multi-component combination can produce a conductive, dielectric and magnetic network structure inside the composite material. The three network structures are spatially interlaced to form a micro-network structure-enhanced ternary composite absorber. This type of ternary composite absorber can bring about the synergistic loss of conductivity, dielectricity and magnetism to the absorber, thereby improving the electromagnetic wave loss capacity. At the same time, the multi-component material can bring about multiple heterogeneous interfaces, which can make a large number of free electrons gather on their horizontal planes, significantly promote the interface polarization effect, and thus improve the electromagnetic wave attenuation. By changing the amount of SiC added and the amount of Ni impregnation, the content of the dielectric component and the magnetic component is controlled, so as to obtain a SiC / NFG / Ni high-efficiency absorber with excellent mechanical properties and wave absorption characteristics, and reveal its wave absorption mechanism. As shown in Example 4, when the NFG:SiC ratio is 4:1 and the matching thickness is 1.5 mm, the composite absorbing material has the best electromagnetic absorbing performance, with a minimum reflection loss of -44.04 dB and an effective absorption bandwidth of 5.42 GHz (8.24-13.68 GHz).
[0007] Wave absorption mechanism: First, the synergistic effect of high dielectric and low magnetic permeability is used to regulate electromagnetic parameters, optimize impedance matching, and realize the absorption of electromagnetic waves. Second, due to the multi-layered and porous structure of the porous graphite ceramic preform itself, the incident electromagnetic wave is reflected and scattered multiple times in the absorbing material, resulting in the loss of electromagnetic waves. Third, SiC, graphite, Ni and resin will form multiple heterogeneous interfaces, and a large number of free electrons will gather on their interfaces, thereby triggering the interface polarization effect and enhancing the attenuation ability of electromagnetic waves. Fourth, the vacancy defects in the polarization centers of silicon carbide, nickel and NFG will lead to the polarization of the electric dipole moment. At the same time, in the external field, a large number of unpaired electrons will move, resulting in the transmission of electrons, triggering conduction losses, and thus increasing the loss of electromagnetic waves.
[0008] Figure 2 This is a scanning electron microscope (SEM) image of a resin-based silicon carbide / graphite / nickel composite material, where the ratio of impregnant to nickel powder is 1:1. Figure 2(b) It can be seen that the impregnated EP containing Ni micropowder is uniformly distributed in the micropores formed during the SLS process. However, with the increase of SiC content, the number of pores becomes smaller and the pore size becomes larger, resulting in the partial agglomeration of the impregnated EP containing Ni micropowder on the surface of the graphite matrix. Figure 2 (a) and (c) clearly show that natural flake graphite / SiC / MC is embedded in the impregnated EP, and the amount of impregnated EP also changes with the addition of SiC. The resin and natural flake graphite act as carriers for dielectric particles SiC and magnetic particles Ni, so that SiC, Ni and NFG form a three-dimensional interwoven network structure, thereby promoting the synergistic effect of magnetic loss, dielectric loss and conductive loss. At the same time, multiple heterogeneous interfaces enhance the interface polarization, multiple reflections and scattering of the composite material. Figure 2 (e) shows the EDS mapping image of the S-1 sample, in which the proportion of C and O elements is the largest because the main components of the matrix are NFG, PF and EP. In addition, Si and Ni elements are well dispersed in the matrix, indicating that SiC, MC and Ni are uniformly distributed in the composite material.
[0009] The present invention achieves the above object by: (1) Mixed powder Graphite powder, silicon carbide powder, mullite powder and phenolic resin solution are weighed in a certain proportion and put into a powder mixer in batches. After being fully ball-milled and evenly milled, they are taken out and dried, and then sieved, mixed and crushed, and sieved to obtain composite powder.
[0010] The graphite has a carbon content of 99.99% and a particle size of 150 to 300 meshes; silicon carbide powder (purity: 99%, particle size: 30 μm); mullite powder particle size ranges from 300 to 450 meshes; and the phenolic resin liquid model is 2130. The ball mill speed is 300 to 850 r / min, the ball milling time is 4 to 5 hours, and the drying is carried out in an electric constant temperature blast drying oven, the temperature is set at 100 to 150 ° C, the drying time is 1 to 1.5 hours, and the mesh size is 200 to 300 meshes.
[0011] (2) Preparation of porous graphite blank The prepared composite powder was placed on a selective laser sintering machine, and the composite powder was prepared into a porous graphite blank by laser sintering technology. Among them, the selective laser sintering machine (model: HK-S500, Wuhan Huake 3D Technology Co., Ltd.) had the following process parameters: laser power 16-18 W, scanning speed 2300-2500 mm / s, scanning spacing 0.1-0.2 mm, layer thickness 0.1-0.2 mm, and preheating temperature 30-40 °C.
[0012] (3) Secondary curing The preform was then placed in an oven for secondary curing. The initial temperature range of the oven was set at 60-180°C, the heating rate was 5°C / min, and the temperature was kept for 15 min every time the temperature was increased by 30°C.
[0013] (4) Vacuum pressure impregnation The impregnating agent is mixed with high-purity nickel powder, and then mixed evenly by a stirrer, and then the preform is immersed in it, and then placed in a vacuum pressure impregnator, and evacuated to below 0.1Mpa, the impregnation pressure is 10-15N, and the impregnation is performed 1-3 times, each time for 4-6 minutes. Among them, the stirring speed is 1100-1300 r / min, and the stirring time is 30-45 minutes.
[0014] Finally, the impregnated sample is taken out and placed in a dry and ventilated place, and after cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1-2 μm, and the epoxy resin solution model is E-44.
[0015] Among them, in the impregnating agent containing high-purity nickel powder, the impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2. The impregnating agent: high-purity nickel powder is 1:0-2.
[0016] The advantages of the present invention are: (1) A new method for preparing absorbing materials, selective laser sintering (SLS 3D printing), is proposed, which can directly realize the rapid prototyping of complex and efficient absorbing materials, with energy saving, environmental protection and low cost.
[0017] (2) Compared with the preparation methods mentioned above, the new method can realize the rapid manufacturing of multi-material, multi-combination, and complex-shaped parts, and can change the size and number of the internal pore structure of the composite material by adjusting the laser power, and each component can be evenly dispersed inside the composite material.
[0018] (3) Due to the huge difference in density between the three materials mentioned above, mechanical ball milling alone is not enough to mix them evenly. Therefore, high-purity nickel powder is evenly introduced into the pores generated by the porous graphite preform by vacuum pressure impregnation.
[0019] (4) In this paper, the absorbing performance of the composite material is regulated by adjusting the content and matching thickness of silicon carbide. When the amount of silicon carbide added is 10 wt% and the content of impregnated nickel powder is 25.06 wt%, the composite absorbing material has the best electromagnetic absorbing performance, with a minimum reflection loss of -44.04 dB and an effective absorption bandwidth of 5.42 GHz (8.24~13.68 GHz), achieving effective absorption of electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1Flow chart for the preparation of resin-based silicon carbide / graphite / nickel composite absorbing materials.
[0021] Figure 2 Scanning electron microscopy (SEM) image of resin-based silicon carbide / graphite / nickel composite.
[0022] Figure 3 (a) Flake natural graphite; (b) Hexagonal silicon carbide; (c) Coaxial rings.
[0023] Figure 4 Diagram of the microwave absorption mechanism of resin-based silicon carbide / graphite / nickel composite materials. DETAILED DESCRIPTION
[0024] The specific embodiments of the present invention are further described below.
[0025] Example 1 The silicon carbide / nickel / graphite composite absorbing material comprises 40 wt% graphite powder, 10 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin. The graphite has a carbon content of 99.99% and a particle size of 300 mesh; silicon carbide powder (purity: 99%, particle size: 30 μm); mullite powder particle size range is 300 mesh; and the phenolic resin liquid model is 2130.
[0026] (1) Mixed powder Graphite powder, silicon carbide powder, mullite powder and phenolic resin solution are weighed in batches according to the above proportions and put into a powder mixer in batches. After being fully ball-milled and uniformly processed, they are taken out and dried, and then sieved, mixed and crushed, and sieved to obtain composite powder.
[0027] The ball mill speed is 300-850 r / min, and the ball milling time is 4-5 h. Drying is carried out in an electric constant temperature blast drying oven, the temperature is set at 100-150 °C, and the drying time is 1-1.5 h. The mesh number of the sieve is 200-300 meshes.
[0028] (2) Preparation of porous graphite blank The prepared composite powder was placed on a selective laser sintering machine, and the composite powder was prepared into a porous graphite blank by laser sintering technology. Among them, the selective laser sintering machine (model: HK-S500, Wuhan Huake 3D Technology Co., Ltd.) had the following process parameters: laser power 17 W, scanning speed 2400 mm / s, scanning spacing 0.1 mm, layer thickness 0.1 mm, and preheating temperature 40 °C.
[0029] (3) Secondary curing The porous graphite blank was placed in an oven for secondary curing. The initial temperature range of the oven was set from 60 to 180 °C. The temperature was kept for 15 min every time it was increased by 30 °C. Finally, the temperature was kept for 30 min to obtain a porous graphite preform.
[0030] (4) Vacuum pressure impregnation The preform is immersed in the impregnating agent, and then placed in a vacuum pressure impregnator, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol at a ratio of 1:2. At this time, the impregnating agent does not contain nickel powder.
[0031] The N-1 sample is composed of 40 wt% graphite, 10 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is not impregnated with Ni powder. When the matching thickness is 3.0 mm, the minimum reflection loss (RLmin) is -33.06 dB, and the effective absorption bandwidth (EAB) is 2.80 GHz.
[0032] Example 2 The silicon carbide / nickel / graphite composite absorbing material comprises 30 wt% graphite powder, 20 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0033] Steps (1), (2), and (3) are the same as those in Example 1 above, and thus their description is omitted.
[0034] (4) Vacuum pressure impregnation The preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and vacuumed to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol at a ratio of 1:2.
[0035] Sample N-2 is composed of 30 wt% graphite, 20 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is not impregnated with nickel powder. When the matching thickness is 2.0 mm, the minimum reflection loss (RLmin) is -29.06 dB, and the effective absorption bandwidth (EAB) is 2.16 GHz.
[0036] Example 3 The silicon carbide / nickel / graphite composite absorbing material comprises 20 wt% graphite powder, 30 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0037] (4) Vacuum pressure impregnation The preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and vacuumed to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2.
[0038] Sample N-3 is composed of 20 wt% graphite, 30 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is not impregnated with nickel powder. When the matching thickness is 4.0 mm, the minimum reflection loss (RLmin) is -14.11 dB, and the effective absorption bandwidth (EAB) is 1.84 GHz.
[0039] Example 4 The silicon carbide / nickel / graphite composite absorbing material comprises 40 wt% graphite powder, 10 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0040] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:1, and then the preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2.
[0041] The S-1 sample is composed of 40 wt% graphite, 10 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 1. When the matching thickness is 1.5 mm, the minimum reflection loss (RLmin) is -44.04 dB, and the effective absorption broadband (EAB) is 5.42 GHz.
[0042] Example 5 The silicon carbide / nickel / graphite composite absorbing material comprises 30 wt% graphite powder, 20 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0043] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:1, and then the preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1: 2.
[0044] The S-2 sample is composed of 30 wt% graphite, 20 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 1. When the matching thickness is 1.5 mm, the minimum reflection loss (RLmin) is -39.66 dB, and the effective absorption broadband (EAB) is 2.80 GHz.
[0045] Example 6 The silicon carbide / nickel / graphite composite absorbing material comprises 20 wt% graphite powder, 30 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0046] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:1, and then mixed evenly with a blender, and the preform is immersed in it, and then placed in a vacuum pressure impregnator, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and water ethanol in a ratio of 1:2.
[0047] The S-3 sample is composed of 20 wt% graphite, 30 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 1. When the matching thickness is 2.5 mm, the minimum reflection loss (RLmin) is -29.42 dB, and the effective absorption broadband (EAB) is 2.72 GHz.
[0048] Example 7 The silicon carbide / nickel / graphite composite absorbing material comprises 40 wt% graphite powder, 10 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0049] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:2, and then mixed evenly with a blender, and the preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2.
[0050] Sample M-1 is composed of 40 wt% graphite, 10 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 2. When the matching thickness is 2.0 mm, the minimum reflection loss (RLmin) is -38.97 dB, and the effective absorption broadband (EAB) is 3.28 GHz.
[0051] Example 8 The silicon carbide / nickel / graphite composite absorbing material comprises 30 wt% graphite powder, 20 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0052] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:2, and then mixed evenly with a blender, and the preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2.
[0053] Sample M-2 is composed of 30 wt% graphite, 20 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 2. When the matching thickness is 1.5 mm, the minimum reflection loss (RLmin) is -31.52 dB, and the effective absorption broadband (EAB) is 3.72 GHz.
[0054] Example 9 The silicon carbide / nickel / graphite composite absorbing material comprises 20 wt% graphite powder, 30 wt% silicon carbide powder, 20 wt% mullite powder and 30 wt% phenolic resin.
[0055] (4) Vacuum pressure impregnation The impregnating agent and high-purity nickel powder are mixed in a mass ratio of 1:2, and then mixed evenly with a blender, and the preform is immersed in it, and then placed in a vacuum pressure impregnation machine, and evacuated to below 0.1Mpa, the impregnation pressure is 12N, and the impregnation is performed 3 times, each time for 4 minutes. Finally, the impregnated sample is taken out and placed in a dry and ventilated place. After cross-linking and curing, the silicon carbide / graphite / nickel composite absorbing material can be obtained. Among them, the particle size range of high-purity nickel powder is 1 μm, and the epoxy resin solution model is E-44. The impregnating agent is composed of epoxy resin and anhydrous ethanol in a ratio of 1:2.
[0056] Sample M-3 is composed of 20 wt% graphite, 30 wt% silicon carbide, 30 wt% phenolic resin, and 20 wt% mullite. The sample is also impregnated with nickel powder containing epoxy resin, and the ratio of impregnant to Ni is 1: 2. When the matching thickness is 4.0 mm, the minimum reflection loss (RLmin) is -25.18 dB, and the effective absorption broadband (EAB) is 3.28 GHz.
[0057] The weight gain rate and the content of impregnated nickel powder of the last 9 groups of samples are shown in Table 2. The 9 groups of samples were divided into 3 groups of experiments, and the main difference was the comparison of whether or not Ni was impregnated and the content of impregnated Ni. The weight gain rates of the groups with the same material ratio were almost the same, because the porosity of the samples was the same, and the impregnation amount was the same.
[0058] Table 1. Comparison of microwave absorption properties of composite materials
[0059] Table 2 Weight gain rate and impregnation nickel powder content of composite materials .
Claims
1. A method for preparing a resin-based silicon carbide / graphite / nickel composite absorbing material, characterized in that: The preparation process includes the following steps: Step 1: First, weigh graphite powder, silicon carbide powder, phenolic resin solution, and mullite powder, mix them evenly, dry them, crush them, and sieve them to obtain composite powder; Step 2: preparing a porous graphite blank by selective laser sintering the composite powder; Step 3: placing the prepared porous graphite blank into an oven for secondary curing to obtain a porous graphite preform; Step 4: Immerse the porous graphite preform in an impregnating agent containing high-purity nickel powder, perform vacuum pressure impregnation, and obtain a silicon carbide / graphite / nickel composite absorbing material after cross-linking and curing.
2. The method for preparing the resin-based silicon carbide / graphite / nickel composite absorbing material according to claim 1, characterized in that: The carbon content of the graphite powder is greater than 99.99%, and the particle size is 150-300 meshes; the purity of the silicon carbide powder is greater than 99%, and the particle size is 20-30 μm; the particle size range of the mullite powder is 300-450 meshes; and the model of the phenolic resin liquid is 2130.
3. The method for preparing the resin-based silicon carbide / graphite / nickel composite absorbing material according to claim 1, characterized in that: Graphite powder accounts for 25-45 wt%, silicon carbide powder accounts for 10-30 wt%, mullite accounts for 20 wt%, phenolic resin liquid accounts for 30 wt%, and the rest is epoxy resin and nickel.
4. The method for preparing the resin-based silicon carbide / graphite / nickel composite absorbing material according to claim 1, characterized in that: The process parameters during laser sintering are: laser power 16-18 W, scanning speed 2300-2500 mm / s, scanning spacing 0.1-0.2 mm, layer thickness 0.1-0.2 mm, and preheating temperature 30-40 °C.
5. The method for preparing the resin-based silicon carbide / graphite / nickel composite absorbing material according to claim 1, characterized in that: The porous graphite blank is placed in an oven for secondary curing. The initial temperature range of the oven is set at 60-180 °C and the insulation time is 1h-2h.
6. The method for preparing the resin-based silicon carbide / graphite / nickel composite absorbing material according to claim 1, characterized in that: The porous graphite preform is immersed in an impregnating agent containing nickel powder; wherein the impregnating agent is an anhydrous ethanol solution of epoxy resin, and nickel powder is added, and then stirred evenly with a stirrer, the stirring speed is 1100-1300 r / min, and the stirring time is 30-45min; wherein the particle size range of the nickel powder is 1-2 μm.
7. The method for preparing a novel resin-based silicon carbide / graphite / nickel composite material absorber according to claim 1, characterized in that: Under a vacuum degree of less than 0.1 MPa and an immersion pressure of 10 to 15 N, immerse 1 to 3 times, each immersion time for 4 to 6 minutes.
Citation Information
Patent Citations
Method for preparing wave-absorbing ceramic component on basis of 3D printing technique
CN104193345A
Method for preparing porous titanium carbide ceramic in manner of foam dipping-high temperature sintering
CN106830980A
Selective laser sintering 3D printing shielding material and preparation method and selective laser sintering 3D printing shielding member and manufacturing method
CN110666167A
5G-based high-performance electromagnetic shielding material and preparation method thereof
CN111875921A
Preparation method of 3D printing B4C-based composite ceramic
CN116041065A
Cited By
ZrB2-SiC hollow rod composite material, preparation method and application
CN120309368A